(untitled) (Phenomenology, Humanities and Sciences, 2025)
There is a central line of Merleau-Ponty’s thought that begins to develop incipiently from the late 1940s, gains strength and becomes robust during the 1950s, and from that moment until his death in 1961, becomes the fundamental problem of his thought. This line of thought explores the language of literature and its ability to express the sensible world. This inquiry leads him to project The Visible and the Invisible, a study interrupted by his death, in which he was to develop a theory of truth founding a new ontology. The conviction that motivates this book is the supposition that the problem left by Husserl regarding the possibility of bringing mute experience to the expression of its own meaning can be resolved through the exploration of the literary use of language. In this article, we will attempt to reconstruct Merleau-Ponty’s line of thought concerning the language of literature and suggest that it is possible, through a phenomenological inquiry into literature, to establish the foundations for a literary phenomenology.